Strategi Pengembangan Bisnis Menggunakan Pendekatan Business Model Canvas Pada Dapoer Ethak - Irma Cahyani; Paisal; Hendra Sastrawinata (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2024)
Dapoer Ethak is a culinary business that sells various pempek and cakes, located in Kayu Agung District,South Sumatra. The purpose of this research is to (1) analyze the application of production, marketing,human resources and financial aspects as development strategies at Dapoer Ethak (2) analyze how to applythe Business Model Canvas method to Dapoer Ethak's business. This research is descriptive in nature byapplying a qualitative approach. Data collection was carried out using interview, observation anddocumentation methods at the Dapoer Ethak business. Based on the research results, it can be seen that incarrying out its business activities, Dapoer Ethak has implemented aspects of production, marketing, financeand human resources well and fulfilled the 9 elements of the Business Model Canvas. However, itsimplementation is still not carried out optimally and requires improvements to all aspects ofentrepreneurship and elements of BMC to increase its business competitiveness, such as collaborating withsuppliers of raw materials and packaging, improving financial reports, improving the marketing system,actively participating in food & beverage events, employee training, added a diverse drink menu, providinga place to eat in the shop, and upgrading cashier equipment.